The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.cirpj.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Relating properties and functions from patents to TRIZ trends

Abstract: TRIZ trends describe the evolutionary status of a system by identifying the trend phases, and assist in predicting improvements by identifying evolutionary potential. This process encompasses analyzing and categorizing patents in known trend phases, relying on intrinsic skills of a TRIZ expert, and depicting the results on an evolutionary potential radar plot. To structure this approach, an algorithm is proposed that, through patent analysis and identification of word categories, extracts information concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 12 publications
(11 reference statements)
0
26
0
1
Order By: Relevance
“…Among these various sections, the narrative sections can be used to extract binary relations related to properties and functions. Tong et al (2006) and Verhaegen et al (2009) indicated the importance of including titles and abstract in the automatic analysis of patents. Chen et al (2003) regarded the human-generated abstracts of patent documents as the most important part.…”
Section: Patent Collectionmentioning
confidence: 98%
See 3 more Smart Citations
“…Among these various sections, the narrative sections can be used to extract binary relations related to properties and functions. Tong et al (2006) and Verhaegen et al (2009) indicated the importance of including titles and abstract in the automatic analysis of patents. Chen et al (2003) regarded the human-generated abstracts of patent documents as the most important part.…”
Section: Patent Collectionmentioning
confidence: 98%
“…On the basis of these studies, this research uses only abstracts to extract binary relations. Another reason for using abstracts is that they are available in English in most patents (Verhaegen et al 2009). …”
Section: Patent Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…TRIZ was developed mainly using knowledge acquired from engineering patents awarded in all engineering domains and is based on the concept that every superior invention is the result of resolving a contradiction and that technical systems follow generic tendencies throughout their existence, which have been named as the laws of technical system evolution (Altshuller, 1984). TRIZ aims to problem solving in computer aided innovation (Leon, 2009 andVerhaegen et al, 2009). However, a new paradigm was necessary for mechatronic system design.…”
Section: Mechatronic Product Developmentmentioning
confidence: 99%